PRMT5 function and targeting in cancer - Kim, Hyungsoo; Ronai, Ze’ev A. (Cell Stress, 2020)
Protein methyl transferases play critical roles in numerous regulatory pathways that underlie cancer development, progression and therapy-response. Here we discuss the function of PRMT5, a member of the nine-member PRMT family, in controlling oncogenic processes including tumor intrinsic, as well as extrinsic microenvironmental signaling pathways. We discuss PRMT5 effect on histone methylation and methylation of regulatory proteins including those involved in RNA splicing, cell cycle, cell death and metabolic signaling. In all, we highlight the importance of PRMT5 regulation and function in cancer, which provide the foundation for therapeutic modalities targeting PRMT5.